Public Urban Transportation in the Smart City: An Exploratory Study in the Northern México - Reyes, Aida Yarira (Springer International Publishing, 2021)
Upon identifying the troubled system of public transportation in the Northern-border City of Juarez, Mexico, this research adopts an exploratory approach to address such problem and provide a plausible path to solve it. Urban mobility has become one of the main challenges for the Smart City. The latter concept is a global tendency to achieve competitive edge via adopting technological development regarding public mobility. Juarez system of public transportation experiences lacks of modernity infrastructure, which results in pollution due to obsolete vehicles, delays, passenger saturation during heavy hours, traffic accidents and users’ inconveniences. Although many proposals arose in the past to deal with the prevailing situation, to date the city experiences no improvements whatsoever. This paper examines what the scenario would be if the City embarked in the endeavor of adopting high-tech vehicles for public transportation. Particularly, the paper transits through the sate-of-the-art literature to provide in-sights regarding modern transportation alternatives that not only are environmental-friendly, but also financially viable, promoting productive chaining and local benefits. The proposal centers in buses powered by electricity. The paper discusses financial figures and possible scenarios; it also highlights the need for future urban infrastructure improvement and reconfigurations, especially pavement and transportation routes redesign to allocate charging stations.